The impact of uncertainty on macro variables: An SVAR-based empirical analysis for EU countries - Ansgar Belke; Dominik Kronen (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
In light of the rising political and economic uncertainty in Europe, we aim to provide a basic understanding of the impact of economic policy uncertainty and financial market uncertainty on a set of macroeconomic variables such as production, consumption and investment. In this paper, we apply a structural vector autoregressive (SVAR) model to gain first insights that may help to identify avenues for further research based on non-linear processes. We find that stock market uncertainty shows a fairly consistently negative effect on the real economy in Europe. However, the implications of economic policy uncertainty for Europe and the Euro area in particular are not so straightforward. It seems as if policy uncertainty raises general investment and consumption of longlived goods in the EMU core countries in order to be prepared to react on different states of the world in the future. What is more, shifts of investment from peripheral to core EMU member countries as safe havens in uncertain times may produce the same empirical pattern. – – Vor dem Hintergrund der aktuell wachsenden politischen und ökonomischen Unsicherheit in Europa beabsichtigen wir, ein grundlegendes Verständnis des Effekts von politischer Unsicherheit und Finanzmarktunsicherheit auf makroökonomische Variablen wie Produktion, Konsum und Investition zu erlangen. Zu diesem Zweck wenden wir ein Strukturelles Vektorautoregressives (SVAR) Modell an, um erste Hinweise für zukunftsträchtige Forschung unter Rückgriff auf nicht-lineare Prozesse zu erlangen. Wir kommen zu dem Ergebnis, dass Finanzmarktunsicherheit einen durchweg negativen Effekt auf die oben genannten makroökonomischen realwirtschaftlichen Variablen in Europa hat. Die Implikationen politischer Unsicherheit für Europa und die Eurozone im Speziellen fallen hingegen, was das Vorzeichen angeht, nicht so eindeutig aus. Es scheint, als würde politische Unsicherheit allgemeine (im Gegensatz zu spezifischen) Investitionen und den Kauf langlebiger Konsumgüter sogar anregen, um später auf verschiedene Umweltzustände reagieren zu können. Zusätzlich könnte die Verlagerung von Investitionen aus den Peripherieländern hin zu den Kernländern der Europäischen Währungsunion, die als sichere Häfen gelten, dieses empirische Muster erklären.
Keywords: C32; E20; E60; 330; hysteresis; investment-type decisions; macroeconomic performance under uncertainty; economic policy uncertainty; financial uncertainty; option value of waiting; SVAR